2006
DOI: 10.1007/s00709-006-0171-5
|View full text |Cite
|
Sign up to set email alerts
|

Promoter activity of a putative pollen monosaccharide transporter in Petunia hybrida and characterisation of a transposon insertion mutant

Abstract: Summary.For the growth of the male reproductive cells of plants, the pollen, the presence of sufficient sucrose or monosaccharides is of vital importance. From Petunia hybrida a pollen-specific putative monosaccharide transporter designated PMT1 (for petunia monosaccharide transporter) has been identified previously. The present work provides an in-depth analysis and characterisation of PMT1 in the context of pollen development with the GUS reporter gene and an insertion mutant. The promoter of the pollen-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Moreover, Arabidopsis pollen does germinate on agar media containing glucose but lacking sucrose (Sivitz et al , 2008). However, in their analysis of an insertion mutant of one of the MST genes ( PMT1 ) in Petunia hybrida , Garrido et al (2006) found no defect in pollen function. Further study is clearly needed to characterize the physiological function of MSTs in relation to the function(s) of SUTs in pollen.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, Arabidopsis pollen does germinate on agar media containing glucose but lacking sucrose (Sivitz et al , 2008). However, in their analysis of an insertion mutant of one of the MST genes ( PMT1 ) in Petunia hybrida , Garrido et al (2006) found no defect in pollen function. Further study is clearly needed to characterize the physiological function of MSTs in relation to the function(s) of SUTs in pollen.…”
Section: Discussionmentioning
confidence: 98%
“…Because germinating pollen grains and growing pollen tubes have no symplastic connection to surrounding tissue, nutrients, including hexoses, must be transferred into the pollen tube by transporters. Although the functional characterization of hexose transporters is fundamental to our understanding of reproductive biology, studies on this subject are mainly limited to Arabidopsis (Schneidereit et al, 2003(Schneidereit et al, , 2005Scholz-Starke et al, 2003) and petunia (Ylstra et al, 1998;Garrido et al, 2006). Furthermore, it is difficult to assign functions to those transporters because single knockouts in these species do not result in phenotypic change.…”
Section: Csht1 Is a Key Gene For Seed Development Due To Its Control mentioning
confidence: 99%
“…Addition of Glc causes instant bursting of Arabidopsis pollen tubes (Schneidereit et al, 2003(Schneidereit et al, , 2005Scholz-Starke et al, 2003). Similarly, there is no phenotype associated with an insertion mutant of Petunia Monosaccharide Transporter1 (PMT1), a putative pollen-specific hexose transporter, of petunia (Ylstra et al, 1998;Garrido et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…; Garrido et al . ). In Arabidopsis , many pollen‐specific genes have been identified using different molecular approaches (da Costa‐Nunes & Grossniklaus ).…”
Section: Introductionmentioning
confidence: 97%